AN INTEGRATIVE NOTION OF PUNISHMENT IN TRADITIONAL YORUBA CULTURE (2011)
A challenge confronting the study of punishment in contemporary society is the justification of the institution concerned with the deliberate infliction of suffering on an offender. Most of these justifications have been anchored on either of two competing theories, namely the utilitarian and retributivist theories of punishment to the neglect of integrative notion of punishment found among the Yoruba. However, these theories fail to account for some elements necessary for an adequate conception of punishment such as proportional gravitation of punishment and the aversion to punishing the innocent. This study, therefore, examined the notion of punishment within the Yoruba culture, which reconciles the physical and non-physical aspects of human existence, in order to arrive at an integrative notion of punishment. The study adopted the hermeneutic theories of Hans-Georg Gadamer and Jurgen Habermas. Gadamer evolves an interpretive understanding based on the role of tradition and language, while Habermas’ notion of praxis and constitutive interests provides the basis for understanding the constitutive interests and social class structure which determines who exercises what responsibilities in any society. These views thus provide the basis for understanding the dimensions of punishment in Yoruba culture. It also employed the conceptual, critical and constructive methods of philosophy. Data were collected from archival and library materials and subjected to content analysis. The integrative notion of punishment in Yoruba culture goes beyond the discussion of the idea of punishment in western penology within the framework of the utilitarian-retributive debate. It provides for a coherent interconnection among social structure, law and belief system towards the certitude and trust making for harmonious human well- being. Nevertheless, the offender is restitutively reconciled to himself, the victim and the community at large. This underscores the saying that ìka tí ó se ni oba ńgé (It is the finger which offends that the king cuts) to buttress the judicious imposition of punishment on the offender as a means of establishing responsibility for human actions rather than disproportional gravitation of punishment which may degenerate into further antagonism and animosity. Besides, the notion constructively addresses the dispensing of justice in the quickest manner possible against the formal and cold procedural nature of justice. Also, the Yoruba saying bi a ba fi owo òtún na omo eni, a fi t’òsì fà à móra (when a man beats his child with his right hand, he should draw him to himself with his left) advances a creative and flexible human activity, whereby human beings are amenable to change and deserve integration into the community, though the social relations might have been breached because the crime still remains in people’s memories. The achievement of social order is enhanced by the integrative notion of punishment in Yoruba culture. Therefore, it is recommended that this approach should be incorporated into the adjudicatory system in contemporary penal practice.